The assessment of peat physico-chemical properties and carbon stocks in Resak Tambahan peat swamp forest, Pahang - Muhamad Tajudin, Nur Shuhada; Azian, Mohti; Mohd Husin, Hyrul Izwan; Misman, Muhamad Afizzul; Jamaludin, Nurul Mayzaitul Azwa (Malaysian Society of Soil Science, 2025)
Conserving tropical peat forests with high carbon density is among the most cost-effective strategies for addressing global climate change. However, large areas of these forests have historically been impacted by land-use changes, logging, and other human activities, leading to substantial carbon emissions into the atmosphere. This study quantified the physico-chemical properties and soil carbon stocks in a total of nine (9) different compartments representing three (3) different categories of forest; which were high, medium and low density forest located in the district of Rompin, Pahang in order to assess the differences between them. Collected samples were analysed for the physical characteristic; bulk density, total porosity, moisture content and chemical properties; ash content, loss of ignition and organic carbon content. The results showed minimal variation, with most parameters exhibiting similar trends across all densities. Consistency in pH, bulk density, moisture, organic carbon content, and loss on ignition indicates that, despite varying forest densities. The soil carbon stock for the high, medium and low density forests were 329.48  62.25 (C t/ha) 328.50  64.71 (C t/ha) 326.46  48.79 (C t/ha), respectively. Statistical analysis by using ANOVA followed by multiple mean comparison showed no significance difference were observed among the carbon stock value between the three categories of forest. Comprehensive understanding of the variability of the peat properties within the studied area is essential for developing effective strategies for their conservation and sustainable management.